Acute unstable complex radial head and neck fractures fixed with a mini T-shaped plate in a 20-year-old man: a case report - Yu W; Hu J; Zhang X; Zhu X; Xu Y; Yi J; Liu Y (Dove Medical Press, 2016)
Weiguang Yu,1,* Jun Hu,1,* Xinchao Zhang,2 Xingfei Zhu,2 Yinfeng Xu,1 Jianhua Yi,1 Yunjiang Liu1 1Department of Orthopedics, The First Affiliated Hospital of Sun Yat-sen University, Guangzhou, Guangdong, 2Department of Orthopedics, Jinshan Hospital, Fudan University, Shanghai, People’s Republic of China *These authors contributed equally to this work Abstract: Acute unstable complex radial head and neck fractures in adults are seldom reported in the literature. Early recognition and appropriate management are essential to prevent long-term consequences of the loss of elbow function, forearm rotation, and chronic pain. Here, we describe an unusual case of a 20-year-old man who exhibited acute unstable complex fractures of the head and neck of the right radius without other injuries or comorbidity. An open reduction and mini T-shaped plate fixation were performed within 3 hours after injury, and the results were satisfactory. A long plaster fixation was continued for 3 weeks. A gradual mobilization was started after the removal of the plaster under the supervision of a physiotherapist. At the 12-month follow-up, no complications associated with the use of the mini T-shaped plate were noted, and the Mayo Elbow Performance Score was 97 (excellent). To our knowledge, acute unstable complex radial head and neck fractures in adults can be successfully treated with a mini T-shaped plate reconstruction technique. Keywords: unstable complex fractures, mini T-shaped plate, radial head, internal fixation, radial head replacement